Faecal volatile organic compounds analysis using field asymmetric ion mobility spectrometry: non-invasive diagnostics in paediatric inflammatory bowel disease. (28th November 2017) - van Gaal, Nora; Lakenman, Rozanne; Covington, James; Savage, Richard; de Groot, Evelien; Bomers, Marije; Benninga, Marc; Mulder, Chris; de Boer, Nanne; de Meij, Tim
Abstract: Background and Objectives : Inflammatory bowel disease (IBD), including Crohn's disease (CD) and ulcerative colitis (UC), remains challenging to diagnose. Diagnostic work-up carries a high burden, especially in paediatric patients, due to invasive endoscopic procedures. IBD is associated with alterations in intestinal microbiota composition. Faecal volatile organic compounds (VOCs) reflect gut microbiota composition. The aim of this study was to assess the diagnostic accuracy of faecal VOC profiling as a non-invasive diagnostic biomarker for paediatric IBD. Methods : In this diagnostic accuracy study performed in two tertiary centres in the Netherlands, faecal VOC profiles of 36 de novo, treatment-naïve paediatric IBD patients (23 CD, 13 UC), and 24 healthy, matched controls were measured by field asymmetric ion mobility spectrometry (Owlstone Ltd, Lonestar®, UK). Results : Faecal VOC profiles of de novo paediatric IBD patients could be differentiated from healthy controls (AUC ± 95% CI, p-value, sensitivity, specificity; 0.76 ± 0.14, p < 0.001, 79%, 78%). This discrimination from controls was observed in both CD (0.90 ± 0.10, p < 0.0001, 83%, 83%) and UC (0.74 ± 0.19, p = 0.02, 77%, 75%). VOC profiles from UC could not be discriminated from CD (0.67 ± 0.19, p = 0.0996, 65%, 62%). Conclusion : Field asymmetric ion mobility spectrometry allowed for discrimination between faecal VOC profiles of de novo paediatric IBD patients and healthy controls, confirming the potential of faecal VOC analysis as a non-invasive diagnostic biomarker for paediatric IBD. This method may serve as a complementary, non-invasive technique in the diagnosis of IBD, possibly limiting the number of endoscopies needed in children suspected for IBD.